PENGEMBANGAN E-LEARNING SEBAGAI MEDIA PEMBELAJARAN INOVATIF BERBASIS WEBSITE MATA PELAJARAN ADMINISTRASI SISTEM JARINGAN DI SMK - Trianto, Rudi; Nurjanah, Nunung; Herwanto, Heru Wahyu (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research aims to (1) develop learning media, (2) test the level of feasibility of e-learning website-based learning media products, and (3) test the effectiveness of developing e-learning website-based learning media in the Network Systems Administration subject for students class XI TKJ Islamic Vocational School 1 Blitar. This research is research into the development of the ADDIE development model. The data analysis used is in the form of a questionnaire with four scales and test questions in the form of pretest and posttest. The data analysis technique uses descriptive qualitative and quantitative analysis with averages. The feasibility assessment from media experts, namely from lecturers and teachers, the average was 3.72 in the "very feasible" category. The assessment from material experts, the average was 3.57 in the "very feasible" category. The feasibility assessment of 14 students with an average score of 3.30 was categorized as "very feasible" which shows that e-learning is classified as very good. The effectiveness of the media is shown from the results of the pretest and posttest. It shows that effectiveness for the experimental class is shown by a significant increase in scores, while for the control class there is a less significant increase seen from the results of the pretest and posttest.